Histopathological features of subcutaneous mycosis: a retrospective study - Subhashini R.; Ramachandra V Bhat (Tropical Journal of Pathology and Microbiology, 2019)
Background: Subcutaneous fungal infection is commonly seen in tropical and subtropical countries particularly in India. The lesions are usually presented as swelling, in the localized form. Subcutaneous mycosis is caused by penetration of causative fungi into the subcutaneous tissue. Histopathology is one of the main tools of diagnosis in mycology as it has the advantages of early diagnosis compared to culture, low cost and it provides a presumptive identification of the infecting fungus. It also gives information about tissue reaction and supplement culture report. It gives the idea about the fungus isolated in culture is contaminant or pathogenic. Many a times tissue might be sent in formalin as fungal infection is not suspected clinically. Role of histopathologist is very important in diagnosing these subcutaneous fungal lesions.Material &Methods: A retrospective study was conducted on subcutaneous fungal infections seen between January 2014 to December 2018 in the Department of pathology, IGMC&RI, Puducherry. Twenty-two patients with biopsy proven subcutaneous fungal infections were included in the study. In the present study, the varied histopathological features like type of inflammatory response, presence of granulomas, necrosis, eosinophils and abscess formation were seen in the tissue sections.Results: The most common histopathology feature was giant cell reaction seen in 21 (95.5%) cases, followed by epithelioid cell granuloma in 13(59%) cases and areas of necrosis in 13 (59%) cases. Eight (36%) cases showed numerous eosinophilic infiltration 10(46%) cases of scant eosinophils and 4 (18%) cases showed absent eosinophils. These fungal structures were identified in H&E stain itself in 13 (59%) cases.Conclusion: Histopathological study is most important in subcutaneous mycosis as most of the time diagnosis is unsuspected and delayed because of its rarity and varied presentation. Fungal infection should be suspected in cases with localized cystic swelling. High index of suspicion, careful microscopic examination and special stains are important for accurate diagnosis.